Sharia Insurance For Hajj And Umrah Trip PT. Tri Pakarta Insurance Perspective of DSN-MUI Fatwa - Henny Purwanti; Syamsul Hidayat; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
Hajj and Umrah travel insurance plays a very important role in providing a sense of security and comfort to pilgrims travelling to the Holy Land. The importance of this insurance is not only related to the financial aspect, but also has a great impact on the aspects of health, safety and peace of mind of the pilgrims. The purpose of this research is to examine the Shariah insurance for Hajj and Umrah trips managed by PT Asuransi Tri Pakarta from the perspective of the fatwa of the National Shariah Council-Majelis Ulama Indonesia (DSN-MUI). This study is a descriptive qualitative field research. Data were collected through interviews with representatives of PT Asuransi Tri Pakarta, analysis of DSN-MUI fatwa documents, and literature review related to Sharia insurance for Hajj and Umrah trips. The findings showed that, firstly, the adoption of Sharia principles in the preparation of Hajj and Umrah travel insurance products has provided a strong legal basis for the company. PT Asuransi Tri Pakarta Jakarta ensures that its insurance products comply with the provisions of Fatwa DSN-MUI, which allows the use of insurance while avoiding elements of usury and speculation. Additionally, the implementation of sharia-compliant insurance for Hajj and Umrah trips by PT Asuransi Tri Pakarta Jakarta fulfils the needs of pilgrims in facing certain risks that may arise during the journey. Protection against risks, such as trip cancellation, delay, or loss of valuables, provides a sense of security and comfort for pilgrims. This allows them to focus on the implementation of worship without the burden of excessive worry.